Microangiopathic complications in type 1 diabetes mellitus: differences in severity when isolated or associated with autoimmune polyendocrinopathies - Monteagudo, Patrícia Teófilo; Freire, Maria Beatriz Sayeg; Moraes, Nilva Simeren Bueno de; Dib, Sérgio Atala (São Paulo Medical Journal, 1998)
CONTEXT: The development and evolution of different chronic diabetic complications may present variations among the different types and conditions of this disease. OBJECTIVE: To evaluate the degree of microangiopathy in Type 1 diabetes mellitus (DM1) associated with autoimmune polyendocrinopathies (OSAD) or isolated DM1 (iDM1). PATIENTS: OSAD (n=17) and iDM1 (n=13) were over 15 years old at diagnosis of DM and were matched for diabetes duration (13.9 ± 8.2 and 13.2 ± 5.9 years, respectively) and metabolic control (HbA1c: 6.4 ± 1.9 and 6.8 ± 1.4%). MAIN OUTCOME MEASURES: Urinary albumin excretion (UAE; ELISA), the inversion of serum creatinine (1/C) level and indirect ophthalmoscopy. RESULTS: Although the prevalence of hypertension was similar in both groups, the OSAD had inferior levels of UAE (7.4 ± 2.5 vs. 17.3 ± 9.2 µg/min; p< 0.05). Nephropathy was detected in 12% of the OSAD (none of them macroproteinuric) and in 39% of the iDM1 . The UAE in the iDM1 correlated negatively with 1/C values (r= -0.7, p< 0.005), but the same did not occur in the OSAD (r= 0.2, ns). Among patients with retinopathy, the severe form was found in 29% of the OSAD and in 46% of the iDM1. CONCLUSIONS: OSAD was associated with a lower degree of microangiopathy, in spite of age at diagnosis, duration of diabetes and the metabolic control. In contrast with the iDM1 , the increase in UAE of OSAD was not associated with reductions in GFR.